Edward R. Murrow speaking with Abram Sachar (right) and an unidentified man at Brandeis University (Waltham, MA) (Tufts Archival Research Center, 2005)
8x10. Commencement at Brandeis University, June 7, 1959. Edward R. Murrow received an honorary degree (LL.D.).